Kebijakan Luar Negeri U-turn Yordania Terhadap Suriah Pasca-Perang Melawan Terorisme - Dyah Purbo Arum Larasati (Indonesia Center for Middle East Studies, 2021)
Jordan is one of the Arab countries that played an essential role in the war in Syria. The battle began with anti-government demonstrations in Syria in 2011, then turned into an armed conflict after forming armed militias affiliated with Al Qaeda, and continued with the establishment of ISIS in 2013. Currently, Syria has won the war against terrorism, although terrorist militias still control a relatively small area in Syria. Since 2021, Arab countries that initially supported armed militias have taken foreign policy's u-turn, namely returning to normalization efforts with Syria. This study aims to explain the reasons for the normalization of diplomatic relations carried out by Jordan towards Syria. This study uses Robert D. Putnam's two-level games theory and is carried out qualitatively by collecting data through literature studies and interviews with humanitarian activists in Syria. This study finds that Jordan's foreign policy's u-turn towards Syria has two goals. First, it wants to improve its domestic problems, namely the economic downturn, one of which occurred due to the influx of refugees, security issues, water availability. Second, Jordan wants to achieve international targets, whereas Jordan, a Western ally, wants to reduce Iran's influence in the Middle East region.